Rasulan as a Javanese Slametan Tradition on Compromising the Changing of Society - Sartini, Sartini; Supartiningsih, Supartiningsih; Panani, Sriyulita Pramulia; Damayanti, Adita Nurdia; Triyoga, Anwar Ibrahim (Journal of Urban Culture Research, 2023)
Rasulan is a tradition in Java; it's one form of Javanese Slametan (a ritual meal). This research aims to describe the Rasulan, explains the role of the worldview and how the elements of culture, religion and the spirit of the nationality are compromised and changed therein. This research is a mix of library and field studies, utilizing the theory of worldview. Results show that Rasulan is not a religious tradition, but a harvest celebration, taking the form of gratitude in the agrarian society. It consists of world views of space, time, causality and self-other relationships, which constructs how people practice Rasulan within community life. Compromise in the values of tradition, religion and social life occurs with the incorporation of religious events on respecting and appreciating religious groups in the community. This study contributes to the strengthening of the view that Rasulan is not a religious ritual, but a cultural activity.